2014
DOI: 10.2310/7750.2014.14022
|View full text |Cite
|
Sign up to set email alerts
|

Use of Facebook as a Tool for Knowledge Dissemination in Dermatology

Abstract: Patient-centered groups engaged with their fans most effectively. Engagement is a key determinant of a fan's exposure to the contents of the page and hence a gauge of whether the fans who "liked" the page continue to remain engaged or not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…As an online resource, Facebook Groups meet many Nigerian Medical Laboratory Scientists where they are on Facebook. It also has shown, in K4Health's case, to be associated with high levels of engagement with elearning courses and supports health research that concludes social media can effectively be used for knowledge dissemination (Usher et al, 2014;Kim & Vender, 2014).…”
Section: Discussionmentioning
confidence: 76%
“…As an online resource, Facebook Groups meet many Nigerian Medical Laboratory Scientists where they are on Facebook. It also has shown, in K4Health's case, to be associated with high levels of engagement with elearning courses and supports health research that concludes social media can effectively be used for knowledge dissemination (Usher et al, 2014;Kim & Vender, 2014).…”
Section: Discussionmentioning
confidence: 76%
“…Multiple studies worldwide have shown a positive correlation of patient care with usage of the social media by the healthcare professionals [26]- [28]. Our study has tried to analyze the knowledge, attitude and practice of the healthcare professionals to-wards this social media and its advantages in patient care.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of measuring and being cognizant of the level of engagement that Facebook tools devoted to dermatology have with their online users has been recognized and discussed in the literature 12 ; the more engaged a user is with the content material, the more frequently the material is delivered to the user's online interface. 13 The converse is true: the less often a user engages with the material by liking, sharing, or commenting on a post, the probability that material published in the future by the online platform is delivered to the user's interface is gradually reduced over time.…”
Section: Discussionmentioning
confidence: 99%